Agresividad en estudiantes de la Universidad Nacional de Chimborazo - Villacres Godoy, Domenika Mishell (2022)
The current investigation aims to establish the levels of aggressiveness and compare the results between male and female students of Psychopedagogy career at National University of Chimborazo. Aggressiveness is a kind of manifestation where the nature of the individual is shown and it occurs almost constantly and permanently; in other words, the personality is shown in order to harm another person or oneself. The Methodology used included a quantitative approach, non-experimental design, the type of crosssectional study, for the descriptive and comparative character level, for the basic objective and for the field location. The population was the students at the National University of Chimborazo, the sample was 262 students of the Psychopedagogy Career. For data collection, the psychometric instrument called the Modified Aggressiveness Questionnaire (Buss-Durkee) was used; Subsequently, the IBM SPSS statistics 26.0 program was used for data analysis, where it is concluded that the students of the psychopedagogy career at the National University of Chimborazo have a low level of irritability with 42.75%, an average level of verbal aggressiveness with 38.55%, a low level of physical aggressiveness with 38.17%, a low level of resentment with 46.95%, a medium level of suspicion with 38.93%; finally through comparison of results, it is determined that women are more aggressive than men according to the high levels found in the dimensions: irritability, verbal aggressiveness, indirect aggressiveness, resentment and suspicion, men have a high level of aggressiveness physical.